Analysis of professionals and family foster care on advantages and difficulties of visits between foster children and their biological families - Salas-Martínez, María Dolores; Bernedo-Muñoz, Isabel María; Fuentes, Mª Jesús; García-Martín, Miguel Ángel (My University, 2016)
Contact between a foster child and birth parents play an important role in relation to the foster child’s wellbeing. The main aim of this study is to give voice to social workers and foster families about contact visits. This research is part of a project financed by the regional government of Andalusia (Spain) (SEJ-7106) regarding contact visits in foster care. Two focus groups were organized, one with 8 social workers from four foster care agencies and another with 8 foster carers (4 were recruited through the Association of Foster Families in Andalusia and 4 through fostering agencies). Access to foster care agencies and foster families was obtained through the official Andalusian Child Protective Services (SPM). The focal groups were audio-recorded. Transcripts (of the two focus groups gave rise to primary documents for the hermeneutic unit under study. All this information was exported from an Excel database to the ATLAS.ti v7.0 software. The transcripts were examined using an inductive method of open coding in order to identify themes among participants’ responses. Results show that both groups agreed on the utility of visits to maintain the children’s attachment to their birth family, to bring a greater sense of continuity to the children’s life story, to enhance the psychological wellbeing of the foster children and to know the real situation of their birth family. In relation to the difficulties remarked in the course of the visits, one of the issues mentioned by both groups refers to a lack in the coordination among the social workers, the SPM and the foster families involved. The other issue brings together several complaints to the SPM, such as the fact of not providing information about taking decisions regarding the future of the child; the lack of support and preparation of the foster carers, the children and the birth families about visits; as well as the shortage of social workers and economic aids provided by the SPM. The conclusions of this study highlight the need to improve contact visits by developing intervention strategies targeted at all those involved (foster children, family foster care, birth family and social workers). These findings have important implications for practice.
Keywords: Acogimiento familiar; Focal groups; Family foster care; Social workers; Visits